Immunological castration of male mice by a totally synthetic vaccine administered in saline. - Carelli, C (1982)
It had been reported that immunological neutralization of the hypothalamic luteinizing hormone-releasing hormone (LH-RH) can be achieved by injection of the synthetic hormone, a decapeptide, linked to a carrier and administered with Freund's complete adjuvant. Data presented here demonstrate that the resulting immunological castration can be obtained by administering in an aqueous medium the synthetic decapeptide directly conjugated to the synthetic immunomodulator glycopeptide N-acetylmuramyl-L-alanyl-D-isoglutamine. In the group receiving the conjugate, a higher titer of anti-LH-RH antibodies was obtained than in the group receiving LH-RH in Freund's emulsion. Moreover, histological examination showed that seminiferous tubules were atrophied and that no spermatozoides could be observed. This procedure could lead to applications in the veterinary field and also serve as a useful model for other antiviral or antibacterial synthetic vaccines.